The effect of benefits on disability uptake - Christian N. Brinch (Statistics Norway, Research Department, 2009)
I study the effects of the level of disability benefits on disability uptake. Estimation of such effects is difficult because individual levels of disability pension benefits are closely related to individual characteristics that may also affect disability uptake through other mechanisms. I exploit variation in disability benefits related to individual characteristics only through birth cohort, due to special rules of the phasing in of the Norwegian National insurance scheme. These rules imply a nonlinear relationship between birth cohort and disability benefit level, which allows me to estimate the effects of benefits based on between-cohort differences, while controlling for age and year effects and hence implicitly linear trends in birth cohorts. The results show a statistically significant and strong positive effect of benefits on transitions to disability. The robustness of the results is studied in a number of tests based on sample partitions and other groups that are not exposed to the nonlinear relationship between birth cohort and disability benefit level.
Keywords: I38; J22; J26; 330; Disability benefits; disability uptake; instrumental variables.